The Application of Prasi in Balinese Script Writing Learning as an Effort to Introduce Local Wisdom Values in Senior High Schools - Sukma Wirani, Ida Ayu; Rasna, I Wayan; Sutama, I Made; Martha, I Nengah (Proceeding of International Joint Conference on UNESA, 2025)
Culture-based learning can be applied to the learning process to instill the value of local wisdom in the study of the Balinese language using Prasi media. Prasi is an ancient tradition of writing on palm leaves that contains stories about tattwa, tantri, and other knowledge. This study will examine the effectiveness of using Prasi media to learn Balinese script and instill the values of the writing tradition. The study was conducted in class XII.A4 of SMA Negeri 2 Singaraja through classroom action research with a quantitative and qualitative descriptive approach. The subjects of the study were the students of class XII.A4, and the focus of the study was learning to write Balinese script using Prasi media. The results showed that the data collection methods included observation, project assignments, and questionnaires. This study increased understanding of Balinese script writing by 78.4%, and student responses were excellent. This study demonstrated that Prasi media increases students' interest in and ability to write Balinese script, as well as their understanding of the values of the Lontar writing tradition.